(untitled) (TAMADDUN NURI JURNALI, 2025)
This article discusses the socio-philosophical foundations of moral culture. Moral culture is manifested in a person through his behavior. Behavior is the sum of moral actions determined by the consciousness and will of people. The rules of moral culture are the results achieved by humanity through its own experience over the centuries.